Capital Analisys of Micro Small and Medium Enterprises (Convection) Gresik Regency in Sharia Financing Perspective - Deni Yuliatin; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2022)
This research This study aims to examine the meaning of capital in the perspective of sharia financing for convection entrepreneurs in Bungah Distrct, Gresik Regency. By collecting data from 4 informant. The test was carried out using data analysis of the Milles and Huberman model which included data collection, data reduction, and verification. based on the research result of the study indicate that with this debt-based working capital needs can be met, convection entrepreneurs can open and build their business based on loand through sharia financing. Capital in the perspective of sharia financing is funds obtained to meet working capital needs that operate in accordance with sharia principles, where these principles are free and elements or usury. With the capital sourced from sharia financing, the need for fund can be met so that it can improve the welfare of life for convection entrepreneurs in the Bungah sub-district and achieve the smooth establishment of the bisiness.